2014
DOI: 10.5539/ibr.v7n9p67
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Career Growth and Turnover Intention: An Application in Audit Firms in Turkey

Abstract: This study examined the direct effect of organizational career growth on turnover intention, as well as the buffering influence of organizational commitment on this relationship among auditors in Turkey. Organizational career growth was conceptualized by four factors: career goal progress, professional ability development, promotion speed and remuneration growth. Organizational commitment was conceptualized by three components: Affective commitment, normative commitment and continuance commitment. Data was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 37 publications
6
38
0
Order By: Relevance
“…The following Table 3.3.3 further defines the variables of this study and their nature with each question allotted variable wise. (Alam & Muhammad, 2010) Satisfaction with organizational policies and strategies (Independent Variable) 4 items (Alam & Muhammad, 2010) Satisfaction with career development (Independent Variable) 4 items (Karavardar, 2014) Satisfaction with supervisor (Independent Variable) 3 items (Alam & Muhammad, 2010) Satisfaction with compensation levels (Independent Variable) 4 items (Alam & Muhammad, 2010) Satisfaction with task clarity (Independent Variable) With reference to (Mohammad & Alam, 2010) the Cronbach's alpha value for our variables "turnover intention, satisfaction with organizational policies, satisfaction with supervisor, and satisfaction with compensation levels" are all above 0.7. The Cronbach's alpha value for our one of the independent variable "Task Clarity" is 0.73 (Nandal & Krishnan, 2000).…”
Section: Instrumentationmentioning
confidence: 99%
“…The following Table 3.3.3 further defines the variables of this study and their nature with each question allotted variable wise. (Alam & Muhammad, 2010) Satisfaction with organizational policies and strategies (Independent Variable) 4 items (Alam & Muhammad, 2010) Satisfaction with career development (Independent Variable) 4 items (Karavardar, 2014) Satisfaction with supervisor (Independent Variable) 3 items (Alam & Muhammad, 2010) Satisfaction with compensation levels (Independent Variable) 4 items (Alam & Muhammad, 2010) Satisfaction with task clarity (Independent Variable) With reference to (Mohammad & Alam, 2010) the Cronbach's alpha value for our variables "turnover intention, satisfaction with organizational policies, satisfaction with supervisor, and satisfaction with compensation levels" are all above 0.7. The Cronbach's alpha value for our one of the independent variable "Task Clarity" is 0.73 (Nandal & Krishnan, 2000).…”
Section: Instrumentationmentioning
confidence: 99%
“…The work further concluded that, career related factors such as increase in remuneration growth, perceived fair and just appraisal, are some of the major parameters for reducing employee turnover intention. The work of Karavardar (2014) also found an inverse significant relationship between remuneration growth and employees' turnover intention. Growth in remuneration is thus pivotal for employees' sustainability; as an employee is growing, his/her responsibilities will also be increasing.…”
Section: Discussionmentioning
confidence: 88%
“…Nouri and Parker (2013) found that career growth opportunities influence employees' job commitment and reduce their turnover intention. Similarly, Karavardar (2014) identified favourable career growth as one of the major tools for retaining employees in an organisation, and consequently reduce their turnover intentions.…”
Section: Career Growth Opportunities and Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale presents the turnover intention as the outcome or end result of a process, although it does not identify the specific causes. Although the scale developed from the study of conflicts within the family structure, researchers such as Karavardar (2014) have applied it to measure employee turnover intention efficiently. A fall in business activities may be gradual but the effects can to effect after a sufficient period of time (Smith, 2008).…”
Section: Turnover Intentionmentioning
confidence: 99%